Water quality assessment of River Kabul at Peshawar, Pakistan: industrial and urban wastewater impacts - Ullah Zahid; Khan Hizbullah; Waseem Amir; Mahmood Qaisar; Farooq Umar (Химия и технология воды, 2013)
Untreated wastewater discharges may have significant short term and long term effects on the quality of a river system. Present study was undertaken to assess the present status of the water quality of River Kabul near Peshawar in Pakistan. Seven sites were sampled upstream and downstream in River Kabul in 2009. Samples were also taken from waste water channel (Budni Drain) that carries wastewater of Peshawar Industrial Estate as well as the domestic sewers to assess the pollution contribution of these sources to River Kabul. Physico-chemical and microbiological parameters of the samples were analyzed during the study, as well as possible sources of contamination were investigated. The study showed that the pollution level in river is rising from upstream (at city entrance) to downstream (at city exit) due to discharge of domestic waste water effluents, agricultural activities, and solid waste dumping directly into the river.